Concurrence of multiple cutaneous malignancies on sun-exposed vitiligo skin of a patient: A case report and review of the literature - Xiao Ting Zhang; Xin Hua Ma; Wan Wan Jin; Shi Sheng Chen; Hai Ting Xu (Wolters Kluwer Medknow Publications, 2018)
There are very few published studies in the literature examining the association between vitiligo and skin cancers and only some anecdotal reports about phototherapy-associated nonmelanoma skin carcinoma (NMSC) in patients with vitiligo. Herein, we report a case of an 84-year-old male with widespread vitiligo with concurrent onset of two primary cutaneous malignancies in sun-exposed vitiligo skin. The association between vitiligo and NMSC deserves further assessment. Chronic sun damage might be a possible causative factor for the development of NMSC in the vitiligo patient.